Rancang Bangun Aplikasi Knowledge Management Multimedia Dalam Proses Pengembangan Video Pendidikan Pada Bpmtv Surabaya - Baskoro, Rizky Tirtahana; Sunarto, M. J. Dewiyani; Sagirani, Tri (Jurnal JSIKA, 2012)
In the development of educational videos, training and learning is a very important activity. But the experience, knowledge and skills possessed only by the participants in the training so that the absence of learning or knowledge transfer to people who have no knowledge about the training. One reason is the lack of a system that can manage, collect and manage data of existing knowledge into useful information for the development of educational videos.Based on the above, requires a knowledge management system in terms of manufacturing, management, maintenance of data storage is explicit knowledge and tacit knowledge through report creation. Knowledge management system (KMS) is a system that is capable of performing the classification of existing knowledge, how to preserve knowledge, and how to use that knowledge. One solution to overcome the above problems is to create a multimedia knowledge management system.This application can be used by users in obtaining information about knowledge relating to the development of video media for education. This system provides the required knowledge in the form of multimedia files (text, images, documents and videos). This system can also provide statistical reports of users accessing the system, active users, multimedia files are frequently accessed, searched and needed. Keyword: Kata kunci : knowledge, multimedia, video, Knowledge Management System.